Intermediate Outcomes in the Prospective, Multicenter Coarctation of the Aorta Stent Trial (COAST). Issue 19 (12th May 2015) - Meadows, Jeffery; Minahan, Matthew; McElhinney, Doff B.; McEnaney, Kerry; Ringel, Richard
<x xml:space="preserve">Abstract</x> Background— The Coarctation of the Aorta Stent Trial (COAST) was designed to assess the safety and efficacy of the Cheatham Platinum stent when used in children and adults with native or recurrent coarctation. Acute outcomes have been reported. We report here follow-up to 2 years. Methods and Results— A total of 105 patients underwent attempted implantation, with 104 successes. There were no procedural deaths, serious adverse events, or surgical intervention. All patients experienced immediate reduction in upper- to lower-extremity blood pressure difference with sustained improvement to 2 years. Rates of hypertension and medication use decreased from baseline to 12 months and remained largely unchanged at 2 years. Six aortic aneurysms have been identified: 5 were successfully treated with covered stent placement, and 1 resolved without intervention. Stent fractures were noted in 2 patients at 1 year and 11 patients at 2 years, with evidence of fracture progression. To date, only larger stent diameter was associated with stent fracture. Twelve additional fractures have occurred after 2 years. No fracture has resulted in loss of stent integrity, stent embolization, aortic wall injury, or reobstruction. Nine reinterventions occurred in the first 2 years for stent redilation and address of aneurysms, and 10 additional reinterventions occurred after 2 years. Conclusions— The Cheatham Platinum stent is safe and associated with persistent relief of aortic obstruction. Stent fracture and progression of fracture occur but have not resulted in clinically important sequelae. Reintervention is common and related to early and late aortic wall injury and need for re-expansion of small-diameter stents. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00552812.